Which improvements could prevent the departure of the left-without-being-seen patients?. Issue 11 (20th October 2010) - Ibanez, Gladys; Guerin, Luce; Simon, Nicolas
Abstract : Objectives: To determine which measures, other than a reduction in waiting time, could prevent the departure of the left-without-being-seen (LWBS) patients in an emergency department. Secondary objectives were description of the characteristics of LWBS patients, analysis of their reasons for leaving and assessment of their medical outcome. Methods: A feasibility study was used to establish a telephone survey form. A prospective study of 421 patients was then carried out between 23 November 2006 and 12 February 2007 in the Poissy emergency department. Every LWBS patient whose telephone number was available in the administrative file was included. Patients who could not be contacted within 7 days after their departure were excluded. Statistical analyses were performed using STATA 8.0 software. Results: 12 702 patients were admitted to the emergency department, of whom 421 (3.3%) (95% CI 0.030 to 0.036) left without being seen by a physician. 229 patients (54%) agreed to respond to the survey. 56% of the LWBS patients informed the medical team that they were leaving the emergency department. 74% of the surveyed participants suggested measures that could have helped them wait longer. These measures can be separated into two main categories: an improvement in communication and an improvement in the comfort of the emergency department waiting room. Conclusion: The 'quality' of the waiting time appears to be important in the decision to leave. If this aspect was taken into account, a reduction in the number of LWBS patients and improved quality of care could be achieved in emergency departments.